Who Tells Our Story: Intersectional Temporalities in Hamilton: An American Musical. Issue 2 (3rd April 2017) - Silva, Andie; Inayatulla, Shereen
Abstract: This article examines the ways in which Hamilton: An American Musical can be read less as a historical account and more as a prediction of a future immigrant, who is called upon to (re)define US nationhood. Keeping with the tempo of the musical as well as the broader issues of time, space and identity it attempts to address, this article is presented as a dialogical rap. The co-authors' discussion frames Hamilton as an example of the power of unplottable, time-arresting immigrant bodies, to whom the colonial imposition of linear history does not apply. From this framework, the authors' conversation shifts to critiques of racialised tropes running through the production as well as the inaccessibility of theatre tickets. The goal of this dialogical analysis is to invite further debate about the kinds of immigrant time/space travel that make visible questions of agency, representation and access.